Smart dog - Vande Velde, Vivian (Orlando : Magic Carpet Books/Harcourt, 2007)
Fifth-grader Amy finds her life growing complicated when she meets and tries to hide an intelligent, talking dog who has escaped from a university lab.
Ages 8 to 12.
Keywords: Dogs -- Fiction; Human-animal communication -- Fiction